Fundamentals of Entrepreneurship (ENT300) : HANI’s Cupcake / Hashmaimah Abdullah ... [et al.] - Abdullah, Hashmaimah; Mad Suliman, Mohd Azam; Appolonius, Norbert; Ismail, Nurul Izzah (2019)
HANI’s Cupcake is the name of our company. The company is based on the partnership which is consists of the members that hold important position in the company. The main position is such as General Manager, Administration Manager, Marketing Manager, Operational and Financial Manager. The starting capital for the establishment of the company is RM 150,000 where it was from the collection of RM30, 000 from each partnership members of the company itself. The location of HANI’s Cupcake Bakery is in the area of Kolej Seri Gading, UiTM Samarahan Campus 1. We found is as the strategic place to open the business, as it was one of student attraction because it is near to the student’s hostel and nearby with the place where student usually stop by for buying food.